MANAGING PLURALITY TO BOOST HARMONY AMONG RELIGIOUS ADHERENTS IN INDONESIA - Zulkipli Lessy; Isnan Arifin; Cahyaningtias Dwi Prabowo; Muhammad Zaki Mubarok; Asih Rohmatul Listiani; Zahro Ulfaturrohmatiririn (UIN Sunan Kalijaga, 2021)
Indonesia with its pluralities is one of the largest multicultural countries in the world. The pluralities include living religions such as Islam, Christianity, Hindu, Buddha, Kong Hu-chu, and variety of indigenous local beliefs. In Indonesia, keeping religious tolerance is a necessity to ensure social stability from ideological coercion and physical clashes among different communities. Thus, religious difference is not only a blessing but also a recognition and respect of someone toward other faiths and work together in virtue. Of the main findings that difference in religious beliefs is not a driving factor for mutually demeaning, mutually humiliating, or confusing one religion with another. Plurality is an indisputable reality in this archipelago. Therefore, the community must have an attitude for the realization of tolerance in order to yield harmony among religious adherents. The importance of tolerance is to maintain stability, harmony, and tolerance, wisdom, and social benefits. The result of this research is to increase religious harmony in Indonesia by implementing religious tolerance in daily life. With mutual tolerance, it will create a beautiful and peaceful life.